Product Catalogue Using Canva Application as Promotional Media Development for Abajaya Jember MSMEs - Maharani, Agista Kirana; Wardani, Rr. Tri Istining (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The promotional media used by Micro, Small and Medium Enterprises (MSMEs) in Abajaya Jember are currently Offline Store, Instagram. Promotion through offline store is still considered insufficient to attract potential customers because there is no promotional media that can introduce its products to potential Customers so promotional media in the form of product catalogues is needed. The purpose of this study is to create a product Catalogue as an additional promotional media using the Canva application. The research method used is Action Research. Data collection methods include interviews, observations, documentation and questionnaires based on the EPIC model (empathy, persuasion, impact, and communication). The questionnaire was distributed to 15 respondents consisting of 1 business owner, 2 design experts, 2 marketing experts and 10 potential customers. Results from the questionnaire were analyzed using the EPIC model. The study was conducted in 2 cycles. In the first cycle, it showed an EPIC rate score of 3.67, the score was included in the effective good category, but continued in the second cycle because there were suggestions on Catalogue design by design experts. In the second cycle, it shows an EPIC Rate score of 4.4 included in the very effective category, indicating that the Catalogue design of Abajaya Jember MSMEs can attract potential customers. Based on the results of this study, it can be concluded that Catalogue design is said to be effective and feasible to be used to help promotion.